Social Modelling By Cadres Elevates Self Efficacy Of Children About Tuberculosis - Yuniarti, Falasifah Ani; Huriah, Titih; Sofiana, Liena; Satria, Faudyan Eka (Fakultas Kedokteran, 2022)
Introduction -Tuberculosis is one of the main problems of infectious diseases in the world and Indonesia is ranked third in the world. Efforts to prevent transmission are carried out in various ways, both preventive and promotive efforts. Health education is carried out to increase public awareness of this disease. Elementary school students are good targets for increasing knowledge and self-efficacy, so that they can have an early awareness of this disease. Giving material classically is one of the methods used to deliver material about TB to students. This study aims to determine the differences in knowledge and self-efficacy of elementary school students about tuberculosis before and after being given classical material. Methodology - This was a pre-posttest quasi-experiment without a control study. with a target of 52 elementary school students grades 4-6 at SD Kembangan Bantul. The sampling method is total sampling. The intervention given is an hour-long classical offline lecture. The questionnaire developed by the researcher was used to measure the knowledge and self-efficacy of the respondents before and after the intervention. Data analysis using Wilcoxon from the Jamovi statistical program application. Results: there was an increase in the average self-efficacy value after the intervention although it was very low, but the knowledge score between before and after the intervention decreased. Conclusion: The impact of this counseling is that counseling has a positive impact on children's self-efficacy, although it does not have much effect on children's self-efficacy